Implementation of the Teacher Certification Allowance Policy in Nunukan District, Nunukan Regency - Herman Herman; Entang Adhy Muhtar; Rhini Fatmasari (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
The background of this research is that the utilization of teacher certification allowances has not been maximized, has not been able to improve teacher competence, and has not seen the impact of certification on improving learning. This study aims to analyze the implementation of teacher certification allowance policies in Nunukan Regency; including knowing the inhibiting factors and strategies to overcome these obstacles. The theory of policy implementation used is from Van Meter van Horn (1975), which consists of Policy standards and targets; Resources Communication between organizations, Characteristics of implementing agencies; Social, economic and political conditions. The research approach is qualitative using case studies. Data collection techniques through interviews, observation, and documentation. Informants in this study were the Head of the Education Office, the Head of the GTK Department of Education, the Principal, and each school operator. The results showed that the implementation of the teacher certification allowance policy in Nunukan Regency was carried out well, this can be seen from the policy standards and targets that are used as a reference in its implementation, the adequacy of adequate human resources, facilities, and finances. Communication is also carried out well between the education office and the school. The characteristics of implementing agents, social, economic, and political conditions, and dispositions are also going well. The inhibiting factor for the implementation of this policy is that there are still teachers in schools who are unable to fulfill the teaching load 24 hours per week due to limited classes in each school and the additional duties of the teacher, namely as a homeroom teacher, OSIS coach, and extracurricular guidance.